Analysis of the Decision (PN Lubuk Pakam No. 1369/PID.B/2024/PN LBP) in the Perspective of Criminal Procedure Law - Hutabarat, Lina Adinda Krismasuci; Muthia Ivana Zahra; Muhammad Rifai; Dian Wahyu Sembiring; Parlaungan Gabriel Siahaan (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2024)
This study analyzes the court decision in case number 1369/PID.B/2024/PN LBP from the Lubuk Pakam District Court from the perspective of criminal procedural law. Using a qualitative observational research method, the study examines the legal process, application of legal principles, and judicial reasoning in a theft case. Key findings include: 1) The court appropriately applied relevant criminal code provisions on theft; 2) The trial process adheres to criminal procedure principles, including the defendant's rights; 3) The judges provided clear legal considerations based on evidence and witness testimony; 4) The sentencing was proportional and considered mitigating and aggravating factors; 5) The decision demonstrates a commitment to combating theft crimes. Overall, the ruling reflects a fair and transparent application of criminal procedural law in Indonesia's justice system. This analysis contributes to understanding how legal principles are applied in practice in Indonesian criminal cases.